2020
DOI: 10.1136/tsaco-2020-000451
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric trauma primary survey performance among surgical and non-surgical pediatric providers in a Brazilian trauma center

Abstract: IntroductionTrauma is the leading cause of death and disability among Brazilian children and adolescents. Trauma protocols such as those developed by the Advanced Trauma Life Support course are widely taught, but few studies have assessed the degree to which the use of protocolized trauma assessment improves outcomes. This study aims to quantify the adherence of trauma assessment protocols among different types of frontline trauma providers.MethodsA prospective observational study of pediatric trauma care in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It is also used to improve trauma outcomes. Despite widespread ATLS training, pediatric trauma centers often fail to follow the ATLS protocol (4).…”
Section: Introductionmentioning
confidence: 99%
“…It is also used to improve trauma outcomes. Despite widespread ATLS training, pediatric trauma centers often fail to follow the ATLS protocol (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although ATLS training is a foundational trauma education course widely available globally, its impact on reducing the burden of childhood injury deaths in LMICs has not been established. In addition, more than 80% of ATLS‐trained healthcare providers in a Brazilian trauma center requested further targeted education in pediatric trauma [4, 26]. Our research group has also demonstrated poor adherence to ATLS protocols among trauma surgeons when assessing pediatric cases in the setting of an LMIC [4, 26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more than 80% of ATLS‐trained healthcare providers in a Brazilian trauma center requested further targeted education in pediatric trauma [4, 26]. Our research group has also demonstrated poor adherence to ATLS protocols among trauma surgeons when assessing pediatric cases in the setting of an LMIC [4, 26]. Simple clinical interventions such as a checklist were unfortunately shown to be ineffective in the absence of meaningful change in the institutional education program [2, 4, 26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations